Ordering the Potential Anatomy of the Human Body in Betrand Russels Perspective (Critical Study Q.S An-Nahl [16]:78) - Ahmad Askar; Bisri Samsuri; Abdul Aziz Fatkhurrohman (Spiritus: Religious Studies and Education Journal, 2024)
The scientific value of the Qur'an regarding the creation of humans with the gift of physical completeness is one of the undeniable values. In this case, it is narrated specifically in Q.S an-Nahl [16]:78. The verse is also a scientific legitimization in the realm of modern science that proves the factual values of the Qur'an about the potential that Allah gives to humans in sequence after their release from the womb. Based on this, the purpose of this research is to prove the existence of isomorphs between the world of al-Qur'anic language and the world of reality. By using Betrand Russel's logical atomism theory analysis to find the isomorph. The result of this research is that there is an isomorph between the world of language in Q.S an-Nahl [16]:78 and the world of reality as proven by modern medical science that the orderly potential of human anatomy is commensurate with what is narrated in Q.S an-Nahl [16]:78.